2023
DOI: 10.1038/s41598-023-30211-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and pathological factors affecting the hatching success of the two northernmost loggerhead sea turtle (Caretta caretta) nests

Abstract: In recent years, the report of loggerhead sea turtle (Caretta caretta) Mediterranean nesting range has expanded together with new records of nests becoming northward on the Italian coastline of the Tyrrhenian and Adriatic seas. These areas are characterized by intensive human activities, such as tourism, fishery, and marine traffic, all possibly involved in the influence of the use of coastal habitat by marine species. These anthropic threats, in addition to the natural ones and the changing environmental char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In 2021, from the Italian coasts, 244 nests were reported. Specifically, both Campania and Calabria coasts (53 and 77 nesting sites, respectively) have been chosen for turtle spawning (Pietroluongo et al, 2023). However, these beaches are characterised by a high flow of tourism that may threaten eggs and hatchlings, as well as the development of new rookeries.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, from the Italian coasts, 244 nests were reported. Specifically, both Campania and Calabria coasts (53 and 77 nesting sites, respectively) have been chosen for turtle spawning (Pietroluongo et al, 2023). However, these beaches are characterised by a high flow of tourism that may threaten eggs and hatchlings, as well as the development of new rookeries.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that zooplankton, during its grazing activity, cannot distinguish micro and nanoplastics from food, reducing the consumption of organic particles derived from primary producers [25,26]. The entry of plastic nanoparticles into zooplankton organisms is reflected in the impact on large aquatic organisms that ingest zooplankton and indirectly absorb microplastics, causing biomagnification and bioaccumulation [27][28][29]. Indeed, the negative effects of the accumulation of plastics as well as other emerging contaminants such as heavy metals (arsenic, cadmium, and lead) in sensitive target organs such as the gut have been recorded [30].…”
Section: Introductionmentioning
confidence: 99%